Origin of nonthermal emission from the Fermi bubbles and mechanisms of particle acceleration there. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Dogiel, V. A.; Cheng, K.-S.; Chernyshov, D. O.; Ko, C.-M.
Abstract : The discovery of the two giant γ-ray lobes (Fermi bubbles) in the Galactic center (see Dobler et al. 2010 and Su et al. 2010) was one of the most impressive events of the last few years in astrophysics. However, some indications on giant structures in the Galactic center (GC) were observed several years before by WMAP in the radio frequency range between 23 and 33 MHz (Finkbeiner 2004), and by ROSAT in hard X-rays (Bland-Hawthorn & Cohen 2003). Recent observations performed by the Planck Collaboration (Ade et al. 2012) found also lobes in the microwave range which spatially coincided the Fermi bubbles that indicated on the common origin of these phenomena.